Implementation of Problem-Based Learning Model to Improve Student Learning Outcomes in Understanding Zakat at SDN 26 Leupung - Mariana (Jurnal Profesi Guru Indonesia, 2024)
Class action research on V/C students in SD Negeri 26 Leupung on the subject of Understanding Zakat, which is based on initial observations that show the low learning outcomes of students can be seen based on the classical completion percentage of 31.81% with an average of 64.09. The percentage of completion obtained shows a low learning result because it has not reached the classical completion percentage of 80%, so the researcher tries to improve learning by applying the Problem Based Learning (PBL) model to improve the learning results of students. The purpose of this research is to find out if the application of the Problem Based Learning (PBL) model can improve the learning outcomes of class V students in Understanding Zakat in SD Negeri 26 Leupung, and to know how the activities of teachers and students in improving the learning outcomes of students in class V understanding zakat by applying the Learning Model of Problem Based Learning (PBL) in SD Negeri 26 Leupung. This research is a class action research (PTK) that uses qualitative descriptive research methods, namely by analyzing student learning outcomes data and student activity data from cycle I to cycle II. The subjects of this research are students of class V/C at SD Negeri 26 Leupung. Data collection technique through test technique by giving test questions both in cycle I and cycle II. From the analysis of cycle I data, it shows that the learning outcomes of the students have met the criteria of achieving the learning objectives which is 70 and the percentage of classical completion is 80%, this can be seen from the students' scores in cycle I who got a completion score of ≥70 as many as 13 students with a classical completion percentage of 59.09%, with an average of 73.86. While the acquisition of students' grades in cycle II who obtained a completion grade of ≥70 was 19 students with a classical completion percentage of 86.36% with an average of 88.18. Thus, it can be concluded that the application of the Problem Based Learning (PBL) model can improve the learning outcomes of V/C students in the material Understanding Zakat at SD Negeri 26 Leupung.